HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PEREMPUAN DI SMA PASUNDAN 1 KOTA BANDUNG - Rina Rismayanti; Evy Ernawati; Novita Puspita Dewi (Jurnal Ilmiah Kebidanan Imelda, 2025)
According to the World Health Organization (WHO), around 75% of women in the world experience vaginal discharge at least once in their lives, and 45% experience it twice or more. Factors that influence are lack of knowledge and attitudes in maintaining the cleanliness of the feminine area. Some adolescent girls sometimes take this vaginal discharge problem lightly. Thus, efforts are needed to improve knowledge and attitudes about the problem of vaginal discharge. This study uses descriptive correlation with a cross-sectional approach, the sample used was 98 female adolescents in grade XI IPA. The researcher's goal is to determine the relationship between the level of knowledge and attitudes with the incidence of vaginal discharge in adolescent girls. Statistical tests using the Fisher Exact Probability Test with the highest frequency of knowledge, namely the good category of 78 respondents (79.6%), attitude, namely the good category of 75 respondents (76.5%), it is known that the knowledge value is (p = 0.119 > ? = 0.005) meaning that there is no relationship between knowledge and the occurrence of vaginal discharge, while attitude is (p = 0.003 < ? = 0.005) meaning that there is a relationship between attitude and the occurrence of vaginal discharge.